Determination of Antioxidant Activity and Total Anthocyanin Contents of Extracts from Pulp and Peel of Malus domestica - Muhammad Shoaib Khan, Haji; Akhtar, Naveed (Asian Journal of Chemistry, 2012)
Concentration of polyphenolic compounds, such as anthocyanins and the antioxidants in apples (Malus domestica kala kolo) seems to be different with environmental conditions and part of the fruit. Main objective of this study was to quantify the anthocyanin contents and to determine antioxidant activity in peel as well as pulp of apple (Malus domestica kala kolo) which is the best variety found in Pakistan. In this work, antioxidant activity and total anthocyanin contents of apple (Malus domestica kala kolo) pulp and peel extracts were investigated using 1,1-diphenyl- 2-picrylhydrazyl (DPPH) as stable free radical while anthocyanin contents were measured by pH differential method. The result showed that peel has higher scavenging ability on DPPH. At the concentration of 0.10 mg/mL. The DPPH scavenging rates of peel were about 92 % of vitamin C while pulp were about 42 % of it. The results demonstrated different anthocyanin contents in peel and pulp of fruit. The total anthocyanin contents were 95 % and 0.003 % of peel and pulp respectively in comparison to the standard. Anthocyanins have significant contribution to the total antioxidant activity, which varies considerably depending on the part of fruit.